Comparison of the small RNAs of polymerase-deficient and polymerase-positive Rous sarcoma virus and another species of avian retrovirus. - Sawyer, R C (1979)
The small RNAs contained in virions of avian leukosis and sarcoma viruses are a virus-specific subset of the total small RNA population of the host cell. The reverse transcriptase protein must be present in the budding virion for this selection to take place. Virions of the alpha form of the Bryan strain of Rous sarcoma virus, which lack detectable reverse transcriptase, incorporated an unselected population of small RNAs identical to total chicken cell small RNA. Virions of reticuloendotheliosis virus, which contain a reverse transcriptase unrelated to that of the avian leukosis and sarcoma viruses, contained a distinctly different population of small RNAs although both the avian leukosis and sarcoma and the reticuloendotheliosis viruses were grown in chicken cells. Because the primer for avian leukosis and sarcoma virus RNA-dependent DNA synthesis is a host cell tRNA, the differences in reverse transcriptase small RNA selection may help explain the failure of different species of retrovirus to complement for the reverse transcriptase.